KOMUNIKASI GEOGRAFI - Holy Rafika Dhona (Program Studi Ilmu Komunikasi, 2018)
The development of communication and media technology changes spatial formations in human life. A local event becomes a global event in the media network. This condition gave rise to the field of study called by communication geography or media geography. This article is a theoretical review on this field from communication studies perspective. This paper described the growing assumption on the relationship between geography with communication studies. Moreover, this paper explained some basic assumptions of the field and proposed two alternatives the emerging sub-fields according to two scholars; Paul C. Adams and Andre Jansson. In the last, this paper recalled the importance of the field of communication geography in developing communication studies in Indonesia.Keyword : communication, media, communication geography, space/place